Reversible assembly and disassembly of V-ATPase during the lysosome regeneration cycle - Sava, Ioana; Davis, Luther J.; Gray, Sally R.; Bright, Nicholas A.; Luzio, J. Paul (Molecular biology of the cell, 2024)
Regulation of the luminal pH of late endocytic compartments in continuously fed mammalian cells is poorly understood. Using normal rat kidney fibroblasts, we investigated the reversible assembly/disassembly of the proton pumping V-ATPase when endolysosomes are formed by kissing and fusion of late endosomes with lysosomes and during the subsequent reformation of lysosomes. We took advantage of previous work showing that sucrosomes formed by the uptake of sucrose are swollen endolysosomes from which lysosomes are reformed after uptake of invertase. Using confocal microscopy and subcellular fractionation of NRK cells stably expressing fluorescently tagged proteins, we found net recruitment of the V1 subcomplex during sucrosome formation and loss during lysosome reformation, with a similar time course to RAB7a loss. Addition of invertase did not alter mTORC1 signalling, suggesting that the regulation of reversible V-ATPase assembly/disassembly in continuously fed cells differs from that in cells subject to amino acid depletion/refeeding. Using live cell microscopy, we demonstrated recruitment of a fluorescently tagged V1 subunit during endolysosome formation and a dynamic equilibrium and rapid exchange between the cytosolic and membrane bound pools of this subunit. We conclude that reversible V-ATPase assembly/disassembly plays a key role in regulating endolysosomal/lysosomal pH in continuously fed cells.